Informal support needs of cancer patients who are living alone: a qualitative insight. Issue 9 (10th February 2015) - Benoot, Charlotte; Deschepper, Reginald; Saelaert, Marlies; Grypdonck, Maria; Bilsen, Johan
Abstract Objective Staying independent is an important need for cancer patients living alone. Such patients might have specific informal support needs in order to stay independent. We want to explore which informal support patients living alone perceive as helpful along the cancer care continuum. Methods A purposeful sample of 32 patients living alone and undergoing cancer treatment were interviewed, using a semi‐structured interview guide. Seventeen of them were interviewed a second time, 8 months to 1 year later. Analysis was conducted using grounded theory techniques. Results The informal support patients received was not experienced unconditionally positive. We found that an equilibrium was necessary between reducing the disadvantages of living alone while not endangering the advantages of living alone, resulting in a need for an equilibrium between distance and proximity with their informal network. The needed equilibrium was influenced by the patients' history of living alone, the perception of helpfulness of the informal network, the acuteness of side‐effects and prognosis of the disease. We found that, as treatment progressed, patients tended to favor proximity and needed a greater share of the support to be provided by professionals. Conclusions Cancer patients living alone experience informal support as an ambiguous blessing. Such support has to be given in a fine balance in order to be perceived as helpful. Health care providers should educate the informal network of the patient about which support is helpful, and under what circumstances. Copyright © 2015 John Wiley & Sons, Ltd.